Evolution: neuronal control of an archaic mouth - Holstein, Thomas W. (Current biology, 2023)
Cnidarians (corals, hydras, jellyfish, sea anemones) are prey-devouring creatures with a simple nervous system, the function of which is largely unknown. A new study on the freshwater polyp Hydra has now uncovered the neuronal circuits that control its feeding behavior.